The Relationship Between Logistics Capabilities and Customer Attitudes Towards Online Purchasing among Consumers in Malaysia - Lim Yunn Shyuan; Wan Nurul Karimah Wan Ahmad (Research in Management of Technology and Business, 2024)
Online purchasing in Malaysia is demonstrating significant consumer growth. However, customer’s attitude will ultimately determine if a transaction is made and whether to purchase online in the future. The issue is that consumer fears in online purchasing because of late in delivery, non-receipt of products, inaccurate information on delivery time, and poor after sales services. Hence, this study focusses on examining the relationship between logistics capabilities and customer attitudes towards online purchasing among consumers in Malaysia. To achieve the research objective, this study used quantitative approach and a survey was conducted among 384 consumers at the age of 18 years and above in Malaysia with a response rate of 100% where questionnaire-based survey was utilized. Data collected were analysed using descriptive and correlation analysis. The results show that delivery speed, shipment tracking, information quality, and after sales services has a statistically significant positive relationship with customer positive attitudes towards online purchasing. Meanwhile, delivery speed, shipment tracking, and information quality has no statistically significant relationship with customer negative attitude towards online purchasing, whereas there is statistically significant negative relationship between after sales services and customer negative attitude towards online purchasing. Therefore, this study contributes valuable insight and a comprehensive understanding for marketers, e-retailers, and logistics service providers on the relationship between logistics capabilities and customer online purchasing attitudes in Malaysia where logistics capabilities tend to improve customer positive attitudes towards online purchasing.